Building an enterprising generation : an evaluation of the young enterprise scheme : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University - Lewis, Kate (Massey University, 2002)
Enterprise education aims to develop in individuals (particularly the young) a set of skills and/or attitudes that will allow them to be both job creators and job seekers. In the context of the heightened interest in the potential contribution of enterprise education to the 'knowledge economy', the promotion of self-employment as a legitimate work option in schools is evidenced by increasing participation levels in programmes like the Young Enterprise Scheme (YES) (administered by the Enterprise New Zealand Trust). Currently there is little empirical evidence in New Zealand relating to the impact of enterprise education programmes like the YES, or the different ways students manifest the qualities of enterprise. This responsive evaluation of the YES was grounded in the axioms of the naturalistic paradigm. It was based on parallel cycles of data collection that involved observation, interviewing and the dissemination of a questionnaire. Respondents included both adult stakeholders and YES student participants. The evaluation established that the benefits of an experiential, enterprise education opportunity like the YES are wide ranging. They vary from issues of personal development to the accumulation of a portfolio of 'enterprising' skills. It appears that the YES also has some influence on the career intentions and employability of participants. This impact appears more influential on students who are exposed to enterprising role models through their own family or friends. In terms of programme delivery, stakeholders described teachers as the primary influence on how successfully the YES is facilitated. The evaluation identified a number of areas for future research including the role of mentors in the programme, aspects of regional diversity in terms of programme delivery, the need to track the future activities of YES participants, and compare the attitudes and behaviours of YES participants and non-participants. Within the evaluation a transferable framework is proposed for classifying enterprise education programmes in terms of key definitional criteria and proposed programme outcomes.
Keywords: Success in business; Student-owned business enterprises; Entrepreneurship; New Zealand; Secondary education; Young Enterprise Scheme (YES)